Repurposing benzimidazole and benzothiazole derivatives as potential inhibitors of SARS-CoV-2: DFT, QSAR, molecular docking, molecular dynamics simulation, and in-silico pharmacokinetic and toxicity studies - Ranjan K. Mohapatra; Kuldeep Dhama; Amr Ahmed El–Arabey; Ashish K. Sarangi; Ruchi Tiwari; Talha Bin Emran; Mohammad Azam; Saud I. Al-Resayes; Mukesh K. Raval; Veronique Seidel; Mohnad Abdalla (Journal of King Saud University: Science, 2021)
Density Functional Theory (DFT) and Quantitative Structure-Activity Relationship (QSAR) studies were performed on four benzimidazoles (compounds 1–4) and two benzothiazoles (compounds 5 and 6), previously synthesized by our group. The compounds were also investigated for their binding affinity and interactions with the SARS-CoV-2 Mpro (PDB ID: 6LU7) and the human angiotensin-converting enzyme 2 (ACE2) receptor (PDB ID: 6 M18) using a molecular docking approach. Compounds 1, 2, and 3 were found to bind with equal affinity to both targets. Compound 1 showed the highest predictive docking scores, and was further subjected to molecular dynamics (MD) simulation to explain protein stability, ligand properties, and protein–ligand interactions. All compounds were assessed for their structural, physico-chemical, pharmacokinetic, and toxicological properties. Our results suggest that the investigated compounds are potential new drug leads to target SARS-CoV-2.